CSIG-01. NA-K-CL COTRANSPORTER PROTEIN IN THE PATHOGENESIS OF LOW-GRADE GLIOMAS. (11th November 2019) - Luo, Lanxin; Guan, Xiudong; Begum, Gulnaz; Ding, Dawei; Kohanbash, Gary; Sun, Baoshan; Sun, Dandan
Abstract: Low-grade gliomas (LGGs) present a high incidence of epilepsy, infiltrative growth, resistance to therapy, and high risk of transforming into high-grade gliomas (HGGs). Temozolomide (TMZ) is a conventional chemotherapy drug for adjuvant treatment of patients with high-risk LGGs. Na + -K + -2Cl - co-transporter 1 (NKCC1) regulates cell volume and intracellular Cl - concentration which promotes glioma cell migration, resistance to TMZ, and tumor-associated epilepsy. Our new bioinformatic analysis of TCGA and CGGA datasets shows that LGGs expressed higher SLC12A2 gene mRNA (encoding NKCC1 protein) than HGGs, which was confirmed at NKCC1 protein levels. In syngeneic mouse glioma models with intracranial transplantation of two different mouse glioma cell lines (GL26 and SB28), we detected upregulated NKCC1 protein expression in glioma tumor cells as well as in peri-tumor reactive astrocytes in response to TMZ monotherapy. This provided a rationale for us to test the efficacy of combining NKCC1 pharmacological blockade with TMZ on improving therapeutic outcomes. 5-day combination therapy of TMZ with potent NKCC1 inhibitor bumetanide reduced tumor proliferation, potentiated TMZ-mediated apoptosis, and decreased peri-tumor reactive astrocyte formation, which collectively led to suppressed tumor growth and prolonged survival of tumor-bearing mice. Taken together, these results demonstrate that NKCC1 protein plays multifaceted roles in regulating the pathogenesis of LGGs and its blockade presents therapeutic potentials for reducing TMZ-mediated resistance.